Measuring Psychosomatic Disorder in People Liv ing with HIV/AIDS (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
We assessed mental health status and knowledge of, being worried about AIDS. Result- In our study on 17 HIV Positive persons in which 14 were male 3 were female shows 94.11% have shock,76.47% faces stigma, 70.58% faces discrimination, 47.05% faces family violence, 31.83% faces social violence, 41.17% faces family rejection, 64.70% faces social rejection, 88.23% goes in to depression, 76.47% feels loneliness, 100% persons feel fear, 58.82% have suicidal tendency. Conclusion- Based on our review, we suggest that future studies should address the psychological needs of AIDS patients and develop health promotion programs to mitigate the negative impact of parental death on the physical and psychological well being of AIDS patients.
Keywords: HIV/AIDS; Psychosomatic Problems